Research diversity in accounting doctoral education: survey results from the German-speaking countries - Christoph Pelger; Markus Grottke (Business Research, 2017)
US positivistic accounting research is increasingly perceived as having come to be the point of reference for researchers in other countries, including the German-speaking area where formerly normative research was widespread. In this paper, we present the survey results retrieved from 293 doctoral students in accounting in 2009, a period of transition in which old and new approaches to doctoral education co-existed. Specifically, doctoral students were subject to institutional change in the form of more structured doctoral studies and a focus on internationalisation and attempts to publish in academic journals. We find that at that time there was diversity with regard to both the set of accounting journals considered by doctoral students and the methods employed by the latter in their dissertations. With respect to research methods, we show that factors of the institutional setting reflecting a more structured and international approach to doctoral education are in particular linked to empirical quantitative, and to a lesser extent qualitative, research.
Keywords: M41; M42; M49; 650; Accounting journals; Accounting research; Doctoral education; German-speaking countries; Research diversity; Research method